Proceedings of the 2017 Conference on Empirical Methods in Natural Language Processing 2017
DOI: 10.18653/v1/d17-1241
|View full text |Cite
|
Sign up to set email alerts
|

Multi-View Unsupervised User Feature Embedding for Social Media-based Substance Use Prediction

Abstract: In this paper, we demonstrate how the state-of-the-art machine learning and text mining techniques can be used to build effective social media-based substance use detection systems. Since a substance use ground truth is difficult to obtain on a large scale, to maximize system performance, we explore different unsupervised feature learning methods to take advantage of a large amount of unsupervised social media data. We also demonstrate the benefit of using multi-view unsupervised feature learning to combine he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Although some previous studies have provided intriguing approaches to learning representations at the level of words Mikolov, Yih, and Zweig 2013), sentences (Le and Mikolov 2014), and paragraphs (Kiros et al 2015), they are limited in modeling social media content with colloquial relations. Following similar ideas in this work, where discourse and topics are jointly explored, we can conduct other types of representation learning, e.g., embeddings for words (Li et al 2017b), messages (Dhingra et al 2016), or users (Ding, Bickel, and Pan 2017), in context of conversations, which should complement social media representation learning and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies have provided intriguing approaches to learning representations at the level of words Mikolov, Yih, and Zweig 2013), sentences (Le and Mikolov 2014), and paragraphs (Kiros et al 2015), they are limited in modeling social media content with colloquial relations. Following similar ideas in this work, where discourse and topics are jointly explored, we can conduct other types of representation learning, e.g., embeddings for words (Li et al 2017b), messages (Dhingra et al 2016), or users (Ding, Bickel, and Pan 2017), in context of conversations, which should complement social media representation learning and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…25 National survey on drug use and health in 2014 reported that 1 in 10 Americans waged 12 or older had disorders of substances use. 26,27 In the recent years, mass media sites like Facebook, Myspace, and YouTube have grown rapidly to share information to larger population.…”
Section: Media a N D Substances Usementioning
confidence: 99%
“…For tasks other than personality prediction, several studies leverage the textual information derived from user behaviors in social media. Ding et al (2017) applied texts that users liked and posted to predict substance users such as people who drink alcohol. They showed that the distributed bag-of-words (DBOW) models (Le and Mikolov, 2014) achieve good performance.…”
Section: Related Workmentioning
confidence: 99%
“…The first model uses them as BOW features of the SVM classifier and the second model further applies SVD. The third model is a model using DBOW proposed by Ding et al (2017). This model uses words that have appeared ten or more times.…”
Section: Use Of Textual Informationmentioning
confidence: 99%